2021
DOI: 10.1007/s11071-021-06681-z
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear vibrations of rotating pretwisted composite blade reinforced by functionally graded graphene platelets under combined aerodynamic load and airflow in tip clearance

Abstract: The primary resonance and nonlinear vibrations of the functionally graded graphene platelet (FGGP) reinforced rotating pretwisted composite blade under combined the external and multiple parametric excitations are investigated with three different distribution patterns. The FGGP reinforced rotating pretwisted composite blade is simplified to the rotating pretwisted composite cantilever plate reinforced by the functionally graded graphene platelet. It is novel to simplify the leakage of the air flow in the tip … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(4 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…Yao et al [25,26] applied the method of multiple scale to study the nonlinear dynamics of a rotating blade in the case of 1:1 internal resonance and 2:1 internal resonance, respectively. Gu et al [27] investigated the primary resonance and nonlinear vibrations of rotating blades under combined external and multiple parametric excitations. Deepak et al [28] used the formulated spectral element for free vibration and wave propagation analysis of rotating CNT-embedded polymer composite beams.…”
Section: Introductionmentioning
confidence: 99%
“…Yao et al [25,26] applied the method of multiple scale to study the nonlinear dynamics of a rotating blade in the case of 1:1 internal resonance and 2:1 internal resonance, respectively. Gu et al [27] investigated the primary resonance and nonlinear vibrations of rotating blades under combined external and multiple parametric excitations. Deepak et al [28] used the formulated spectral element for free vibration and wave propagation analysis of rotating CNT-embedded polymer composite beams.…”
Section: Introductionmentioning
confidence: 99%
“…In the primary resonance, the second mode could be stimulated, while in the secondary resonance, the frst mode response could be generated. Gu et [22] simplifed the mechanism of the air clearance's airfow leakage into the axial excitation where a steady state plus a small periodic perturbed spinning speed were considered as a transversal excitation. Tey concluded that the oscillations of the O, U, and X patterns of graphenecantilever plate have the largest, second-largest, and smallest amplitudes, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…A simplified mathematical model to study the nonlinear vibrations of rotating composite beams was established by Rafiee et al [21] . Gu et al [22] performed the nonlinear vibration of graphene platelets reinforced pre-twisted composite blades. Li et al [23] reported the nonlinear vibrations of rotating composite shells under arbitrary boundary conditions.…”
Section: Introductionmentioning
confidence: 99%